Tectonic imprints of landscape evolution in the Bhilangana and Mandakini basin, Garhwal Himalaya, India: A geospatial approach. (20th February 2021) - Taloor, Ajay Kumar; Joshi, Lalit Mohan; Kotlia, Bahadur Singh; Alam, Akhtar; Kothyari, Girish Ch; Kandregula, Raj Sunil; Singh, Anoop Kumar; Dumka, Rakesh Kumar
Abstract: Torrential rains, landslides, and seismic activity are the common factors that are causing unprecedented damage to life, property and infrastructure in Mandakini and Bhilangana basins of Garhwal Himalaya. Owing to such conditions, we demonstrate the feedback this landscape in Garhwal Himalaya in response to episodic tectonic uplift and monsoon precipitation. We calculated conventional geomorphic parameters to access the tectonic deformation across the major thrusts and faults. We further analyzed the normalized steepness index (Ksn ), Chi (χ), and knickpoints along the longitudinal course of rivers. Additionally, the study attributed to active nature of Chail/Ramgarh thrust along the Balganga valley as envisaged by five levels of unpaired fluvial terraces, entrenched stream course, river ponding, active and stabilized landslide deposits, etc. Moreover, the flooding during the heavy rainfall events induced river toe cutting makes an effect on settlement over fluvial deposits. Therefore, we suggested that the highly dissected and tilted basins with deep V shaped valleys and ongoing seismicity also fabricates the region more vulnerable for hazards which threaten the human lives.